Comparing engagement markers in economics research articles and opinion pieces: a corpus-based study - He, Mengyu; Hajar Abdul Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Engagement markers which are reader-oriented rhetorical features are used by writers to signal the presence of readers in their writing. As a key rhetorical feature, the use of engagement markers in academic writing has been explored in recent years. Despite this, few studies have compared their use in research articles and opinion pieces. In addition, studies on engagement markers have not drawn extensively on corpus methodology. Given this, the current study explores the use of engagement markers in economics research articles (henceforth RAs) and opinion pieces (henceforth OPs) based on corpus methods from two self-compiled corpora of RAs and OPs. The corpus analysis tool AntConc was used to generate data need for the analysis of engagement markers in the two genres based on Hyland’s (2005b) framework of five types of engagement markers. The results of this study show that there is a higher occurrence of engagement markers in RAs than OPs. Among the different types of engagement markers, directives were predominantly employed by the writers in both genres. The use of engagement markers in RAs and OPs is discussed in relation to the target audiences and different communicative purposes of the two genres. These findings have important implications for English for Specific Purposes (ESP) writing.